Emerging evidence of microbial infection in causing systematic immune vasculitis in Kawasaki disease - Wang, Wang; Zhu, Liyan; Li, Xuan; Liu, Zhiheng; Lv, Haitao; Qian, Guanghui (Frontiers in Microbiology, 2023)
Kawasaki disease (KD) is a systematic vasculitis that is often complicated by coronary artery lesions and is a leading cause of acquired heart disease in developed countries. Previous studies have suggested that genetic susceptibility, together with an inducing infectious agent, could be involved in KD pathogenesis; however, the precise causative agent of this disease remains unknown. Moreover, there are still debates concerning whether KD is an infectious disease or an autoimmune disease, although many studies have begun to show that various pathogens functioning as critical inducers could activate different kinds of immune cells, consequently leading to the dysfunction of endothelial cells and systematic vasculitis. Here in this review, we attempt to summarize all the available evidence concerning pathogen infections associated with KD pathogenesis. in KD. We also discuss the related mechanisms, present a future perspective, and identify the open questions that remain to be investigated, thereby providing a comprehensive description of pathogen infections and their correlations with the host immune system in leading to KD.